Digitalizacija in papir - Možina, Klemen (Knjižnica, 2012)
The paper has always been and it remains to be the primary information carrier though only 0.1% of the total information is recorded on this media. The paper production industry has a great impact on the environment which is mostly due to the use of raw materials (wood of conifers and deciduous trees), fillers (CaCO3), additional materials (dyes, glue, binders, retention aids), and chemicals (acids and bases). However, the greatest impact on the environment is caused by the extensive water consumption. To produce 1 ton of paper up to 60m3 of fresh water are necessary. The water is not the only resource needed in the production cycle. Besides, the consumption of electrical energy (approximately 10,000 MJ/t pap) waste paper (paper represents 35% of waste), and air pollution (paper production and transport) should be taken into consideration. In spite of the above mentioned environmental threats the paper still remains an important element of the everyday life and the use of modern information technology (personal computers, telefax, Internet) has increased its demand and consumption. It is important that the paper is produced from natural materials which are later released into environment without significant environmental consequences. The technology of paper recycling and re-use is widely known and a must of any responsible and professional social environment. Digitisation has increased the consumption of electrical energy as a consequence of production, use and reprocessing of different devices. Unlike a written record, a digital record has no permanentvalue and the electromagnetic field has a negative effect on the digital records. Digital records have to be constantly updated and adjusted to the computer software and hardware. A book and its content represent a treasure and an invaluable part of the cultural heritage. To use a book it is necessary to learn the alphabet whereas to read digital records we need to be computer and information literate. Negative effects of digitisation have affected the production of paper as the demand for graphic paper (newsprint, writing, printing paper) has decreased. The demand for raw materials, products and semi-manufactured products has decreased, too. Consequently, the level of investments in modernisation of equipment and in new production lines has been equally reduced. The proportion of employees directly or indirectly involved in the paper making and paper processing industry has been diminished. In the European Union paper and paper processing industry employ 1.9 million people in 200,000 enterprises representing 6.5% of turnover in the production sector or 80 billion EUR or 16 billion EUR of the value added per year. The EU is expected to prevent the decline of paper and paper related industry (graphic, construction, logistic) which would endanger the production - consumption cycle. After all, dismissals can ruin the social equilibrium. However, the paper production is faced with a difficult situation caused by digitisation. The competitiveness of the global market has an impact on the labour force costs, raw materials and energy products. Besides, production costs within the European Union are not competitive because of the EU Regulations and Directives which affect the price of raw materials, semi products and energy products. All these facts led to the decrease of workforce and the loss of market leading position and competitiveness.
Keywords: papir; papirna industrija; recikliranje; gospodarstvo; economy; digitalizacija; digitization; European Union; Evropska unija